Rhizomelic limb shortness and abnormal facies: short stature syndrome sharing some manifestations with robinow syndrome - Bajaj, Mohit; Sopori, Ayush; Divakaran, Jeevak V; Rao, Naveen; Sharma, Seema (Indian Journal of Case Reports, 2021)
In children, short stature and disproportionate skeletal growth are associated with many syndromes and these syndromes have characteristic radiological changes which help in their diagnosis. However, many of them have no well-defined diagnostic criteria, and thus overlap between apparently distinct syndromes is common. Here, we report a child with characteristic features seen distinct from any other dwarfing syndrome known to us with some of the features similar to Robinow syndrome. Newborn had a broad and prominent forehead, mid-face hypoplasia, hypertelorism, flat nasal bridge, upturned nose, elongated philtrum, protruding tongue, single crease in the left hand, widely spaced nipple, brachydactyly in lower limbs, and disproportionately short rhizomelic upper and lower limbs. Based on these features, a diagnosis of Robinow syndrome was made. The case was the first of his kind admitted to our institute. The diagnosis was made clinically after follow-up.